Scale of WDM transport network using different types of fibers. - Takachio, N.
This paper describes a statistical calculation method for transmission limits taking into consideration dispersion-shifted fiber (DSF) zero-dispersion wavelength deviation for wavelength division multiplexing (WDM) systems employing unequal channel spacing. For example, the upper limit of fiber input power achieving a bit error rate (BER) less than 10-12 shows a 3 dB improvement when the standard deviation is increased from 1 to 8 nm when the transmission distance with a 80 km repeater spacing is 640 km. Furthermore, the network scales employing 1.55 μm DSF, nondispersion-shifted fiber (N-DSF) and conventional single-mode fiber (SMF) are shown. Finally, a method for estimating the transmission limit for a receiver with different sensitivity, different node architecture, and different bit rates is described
Keywords: 1.55 mum; 3 dB; 640 km; BER; WDM transport network; Bit error rate; Conventional single-mode fiber; Dispersion-shifted fiber zero-dispersion wavelength deviation; Node architecture; Nondispersion-shifted fiber; Receiver; Statistical calculation method; Transmission distance; Transmission limits; Unequal channel spacing; Wavelength division multiplexing